ANALISIS KARAKTER DALAM NOVEL THE STARS SHINE DOWN KARYA SIDNEY SHELDON - RAWUNG, ANDRIANO; SIGARLAKI, STEPHANI J.; PAMANTUNG, RINA P. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTSThis skripsi entitled Analysis Characters in the novel The Stars Shine Down by Sidney Sheldon is written to achieve the title of bachelor Degree, there are two main problems to be analyzed, those are “How the characters of the figures in the novel The Strars Shine Down, and what kind’s of figures exist in the novel The Stars Shine Down by Sidney Sheldon. The purpose of this research are to identify the protagonist and antagonist characters found in the novel and analyzed the characters of protagonist and antagonist in the novel The Stars Shine Down by using Robert (1983) theory. For analyzing the data the writer used descriptive method and intrinsic approach. The result of this research show that there are some human characters found in the novel such as introvert, willing, sacrifice, perfectionist, evil, kindness, good relation and wisdom. The characters in this novel can be categorized into protagonist and antagonist characters. Lara Cameron, Howard Keller, Charles Cohn can be categorized as protagonist, characters where James Cameroon, Sean Mac Allister and Paul Martin are as antagonist characters.                                                                                                     Keywords: Characters, Protagonist and Antagonist, Characterization, Novel, The Stars Shine Down.